Implementation of Education Policy in Secondary Schools in Delta State: Challenges and Future Directions (Tamaddun, 2022)
Unqualified teachers, a lack of financing, and the absence of or limited availability of some essential educational facilities are issues encountered in the implementation of education policy. A descriptive research method was used. The purpose of this research is to investigate the challenges and opportunities of educational policy implementation in Delta State public secondary schools. The population consisted of all principals and teachers. The sample size was 62 principals and 260 teachers. Two research questions and two hypotheses guided the study, and the tool for data collection was a questionnaire. The mean and standard deviation were used to answer the research questions while the hypotheses were tested using the Z-test. Findings showed that challenges in implementing education policies include underfunding, irregular classroom supervision, and so on. Among others, it recommended that the government should increase annual budget allocations to education and regular visits to schools by inspectors and supervisors.